Pengaruh Model Cooperative Integrated Reading and Composition (CIRC) Berbantuan Storybooks Terhadap Kemampuan Membaca Pemahaman Peserta didik Kelas IV SDN Karangpring 01 Jember - Jamilatul Bahiro (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This research was motivated by the low reading comprehension skills of students due to teacher-centered learning and the lack of use of interesting learning media. This research aims to determine the effect of the Cooperative Integrated Reading and Composition (CIRC) model assisted by storybooks on the reading comprehension ability of class IV students at SDN Karangpring 01 Jember. This research uses a quantitative approach with a quasi experimental design type. The research subjects consisted of class IV students who were divided into experimental class and control class. Data collection techniques include tests, observation, interviews and documentation. Data analysis was carried out through normality tests, homogeneity tests, and t tests. The results of the research show that the value of tcount > ttable (5.259 > 2.015) with a significance value of 0.000 < 0.05, so there is a significant effect of using the CIRC model assisted by storybooks on students' reading comprehension abilities. The results of the relative effectiveness test show that learning in the experimental class is 21.51% more effective than the control class. The CIRC model assisted by storybooks has been proven to be able to significantly improve students' reading comprehension skills. Keywords: Cooperative Integrated Reading and Composition (CIRC) Learning Model, Storybooks, Reading Comprehension.
Finalisasi 14 Juli 2026_Yudi
Keywords: Cooperative Integrated Reading and Composition (CIRC) Learning Model; Storybooks; Reading Comprehension.